Vitamin E and Antioxidants Content of Portulaca oleracea L. Form Various Altitudes in East Java, Indonesia - F Deru Dewanti; Bambang Pujiasmanto; Sukendah Sukendah; Ahmad Yunus (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2021)
This study aims to obtain purslane plants as a source of local food and a quality bioactive component from various altitudes in East Java, Indonesia. Purslane planting materials were collected from the lowlands <200 m asl in Surabaya, medium plains 200-800 m asl in Malang DAU, and highlands> 800 m asl in Batu, Malang. Analysis of vitamin E was as total tocopherol. The results of the analysis of the content of Portulaca oleraceae L. of vitamin E were as followed: in the highlands 0.1056%, medium lands 0.1253%, and lowlands 1.162%. The analysis showed that Portulaca oleraceae L. could be a source of high quality local food and bioactive components because it contains vitamin E and antioxidants.Keywords: bioactive components; local food; lowland.